Handbook of research on open source software technological, economic, and social perspectives - St. Amant 1970-; Still 1968- (Information Science Reference, 2007)
"This book examines how use of open source software (1S) is affecting society, business, government, education, and law,including an overview of the culture from which 1S emerged and the process though which 1S is created and modified. Readers will gain an understanding of the complexities and the nuances related to 1S adoption and the range of its applications"--Provided by publisher